Numerical investigation on preparation of expanded polymer beads using supercritical CO2 in a spouted bed. (5th March 2023) - Xie, Huihao; Zong, Yuan; Chen, Yichong; Hu, Dongdong; Xu, Zhimei; Zhao, Ling
Highlights: A CFD-DEM model coupled with a bubble evolution model is adopted to investigate the bead foaming process in a spouted bed. Diffusion of CO2 in the polymer matrix is the rate-determining step for the dynamic saturation process. Uniform pressure field during depressurization is beneficial to the uniformity of the prepared expanded beads. Foam morphologies of the expanded beads are strongly related to the saturation pressure and pressure release rate. Abstract: The bead foaming process in a spouted bed is a green way to manufacture expanded beads. A CFD-DEM model has been established to investigate the hydrodynamics behavior in the spouted bed. The simulation results have showed that the establishment of the particle fountain during saturation can effectively disperse the polymer particles and avoid their aggregation. During depressurization, the flow field in the main part of the spouted bed is relatively uniform. Therefore, particles confined within the spouted bed experience similar depressurization profiles, which is beneficial to the uniformity of the expanded beads. Based on the depressurization profiles provided by the CFD-DEM simulation, a bubble evolution model has been built to investigate the effects of operating parameters on the bead foaming results. The simulation results indicate that expanded beads with a narrower cell size distribution can be prepared at a higher saturation pressure rather than a higher pressure release rate.